Physicochemical properties and surface charge characteristics of arid soils in Southeastern Iran - Moghimi, Abolhassan; Jol, Hamdan; Jusop, Shamshuddin; Abd. Wahid, Samsuri; Abtahi, Ali (Hindawi Publishing Corporation, 2013)
The majority of previous studies on surface charge characteristics were done on tropical and subtropical soils. Information of such studies in the arid regions is limited. A study was conducted to investigate the relation between soil chemical and mineralogical properties and surface charge characteristics of an arid region in Southeastern Iran. Eight soil pedons, representing the alluvial and the colluvial deposits, were described, and their mineralogical and physicochemical properties were examined. The common clay minerals in the studied area are smectite, palygorskite, kaolinite, chlorite, and illite. The point of zero charge (pH 0) values are low (2.85-3.35) in all soils mostly affected by organic carbon (OC) and free iron oxide (Fe d). pH 0 has a significant negative correlation with pH under field conditions (r = - 0.45, P < 0.05). The point of zero net charge (PZNC) levels for all the soils were <2, due to the excess negative charge in these soils. The estimated PZNC values were less than pH 0 in all soils because of the high permanent negative charge in these soils. The permanent negative charge (σ p) of the soils studied is high and it has a significant positive correlation with pH, CEC, Na, Mg, SAR, clay content, palygorskite, OC, and Fe d.